Evaluating the EMS and EMU Using Stochastic Simulations : Some Issues - Masson, Paul.; Symansky, Steven (Washington, D.C. : International Monetary Fund, 1993)
Evaluations of European monetary integration using model simulations have given conflicting results, and the paper attempts to elucidate the reasons for the differences. Several features stand out: how to model realignments; how monetary policy is set for individual countries or for Europe; and how large are risk premium shocks in exchange markets. We quantify the effects of different assumptions relating to these features using MULTIMOD.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet